WILL CARBON TAXES HELP ADDRESS CLIMATE CHANGE? - Mintz-Woo, Kian (Les ateliers de l'éthique / The Ethics Forum, 2021)
The coronavirus disease 2019 (COVID-19) crisis ought to serve as a reminder about the costs of failure to consider another long-term risk, climate change. For this reason, it is imperative to consider the merits of policies that may help to limit climate damages. This essay rebuts three common objections to carbon taxes: (1) that they do not change behaviour, (2) that they generate unfair burdens and increase inequality, and (3) that fundamental, systemic change is needed instead of carbon taxes. The responses are (1) that there is both theoretical and empirical reason to think that carbon taxes do change behaviour, with larger taxes changing it to a greater extent; (2) that undistributed carbon taxes are regressive but distributing the tax receipts can alleviate that regressivity (and, in many cases, make the overall effect progressive); and (3) that while small changes for increasing democratic decision-making may be helpful, (fundamental) change takes time and the climate crisis requires urgent action.